Strategi Investasi dan Manajemen Resiko Terhadap Perusahaan Makanan Khas Bukit Tinggi - Eka Hendrayani (Forum Kerjasama Pendidikan Tinggi, 2020)
This study aims to see how strong policies on investment affect the financial aspects of processing a company's risk management strategy, in this study researchers used qualitative methods that display and demonstrate the implementation of a policy that refers to the use of risk management processing in investment policies, corporate finance. In collecting data, several techniques are carried out from interviews, documentation and taking an understanding of problems using the internet, books and journals in the processing of a company's risk management. Analysis of this risk management based approach uses NPV (Net Present Value) Analysis, the results of the study indicate that the project is very feasible to be developed and acted upon in the development of investments that will be carried out by typical Bukit Tinggi food companies